2018
DOI: 10.1007/s00167-018-4854-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and anatomic results of rotator cuff repair at 10 years depend on tear type

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
2
24
1
Order By: Relevance
“…36,50 These results approximate well those of the SOFCOT cohort for the isolated SSp group (19% retear). 2 On the contrary, regarding massive tears assessed by MRI at 9.9 years postoperatively, Zumstein et al 53 reported a much higher retear rate (57%), which comes closer to the figures reported in our studies for C3-C4 tears (SSp nonintegrity, 71%).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…36,50 These results approximate well those of the SOFCOT cohort for the isolated SSp group (19% retear). 2 On the contrary, regarding massive tears assessed by MRI at 9.9 years postoperatively, Zumstein et al 53 reported a much higher retear rate (57%), which comes closer to the figures reported in our studies for C3-C4 tears (SSp nonintegrity, 71%).…”
Section: Discussionsupporting
confidence: 87%
“…In the SOFCOT cohort, RC repair was open in one-half of the patients and arthroscopic in the other. Here the percentage of tendon healing was reported as ranging between 68% and 81%, depending on the initial type of tear, 2 and a separate study by the same study group on massive tears indicated a retear rate of 34%. 8 Interestingly, the differences in the retear rate between isolated SSp tears and larger tears with different extension were not found to be significant, although the failure rate was higher in the group with posterior extension.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Surgical repair of RCTs with these characteristics is often technically challenging and is associated with higher rates of treatment failure or only modest clinical improvement. 1,12 Rockwood et al 43 described irreparable RCTs as those in which a direct repair of the native tendon to its insertion site is not possible. Signs of irreparability include fatty infiltration affecting 50% or more of the rotator cuff musculature, static superior migration of the humeral head, and a narrowed or absent acromiohumeral interval on an upright anteroposterior shoulder radiograph.…”
mentioning
confidence: 99%